Analisis Hukum Perkara BMT BUS Dalam Proses Penarikan Dana Simpanan Anggota - Azhar Rashed; Yessiarie Silvanny Sibot; Dinda Prama Suari (Eastasouth Institute, 2026)
Baitul Maal wat Tamwil (BMT) is a sharia-based microfinance institution that plays an important role in expanding financial access and helping to improve the economy of small communities. However, in practice, legal problems often arise between BMT and its members, particularly in relation to the withdrawal of savings. This study aims to analyze the legal aspects of the BMT BUS case related to the withdrawal of member deposits and to examine the legal protection for members as depositors. This study uses a normative legal research method with a legislative, conceptual, and case study approach. Research data was collected through a literature study of relevant legal sources and analyzed qualitatively. This study shows that the problem of withdrawing member deposits at BMT BUS is caused by weak risk management and disrupted institutional liquidity, so that BMT is unable to fulfill its obligation to return funds in accordance with the agreed contract. Legally, this condition can be categorized as default and reflects the suboptimal legal protection for BMT members. The novelty of this research lies in its legal analysis, which integrates positive law provisions, sharia economic principles, and actual practices in the BMT BUS case. This study is expected to contribute to strengthening regulations, governance, and improving legal protection for BMT members in Indonesia.